Caspase-1 Activation Is Related With HIV-Associated Atherosclerosis in an HIV Transgenic Mouse Model and HIV Patient Cohort. Issue 9 (September 2019) - Kearns, Alison C.; Liu, Fengming; Dai, Shen; Robinson, Jake A.; Kiernan, Elizabeth; Tesfaye Cheru, Lediya; Peng, Xiao; Gordon, Jennifer; Morgello, Susan; Abuova, Aishazhan; Lo, Janet; Zanni, Markella V.; et al.
Abstract : Objective: Atherosclerotic cardiovascular disease (ASCVD) is an increasing cause of morbidity and mortality in people with HIV since the introduction of combination antiretroviral therapy. Despite recent advances in our understanding of HIV ASCVD, controversy still exists on whether this increased risk of ASCVD is due to chronic HIV infection or other risk factors. Mounting biomarker studies indicate a role of monocyte/macrophage activation in HIV ASCVD; however, little is known about the mechanisms through which HIV infection mediates monocyte/macrophage activation in such a way as to engender accelerated atherogenesis. Here, we experimentally investigated whether HIV expression is sufficient to accelerate atherosclerosis and evaluated the role of caspase-1 activation in monocytes/macrophages in HIV ASCVD. Approach and Results: We crossed a well-characterized HIV mouse model, Tg26 mice, which transgenically expresses HIV-1, with ApoE −/− mice to promote atherogenic conditions ( Tg26 +/− / ApoE −/− ). Tg26 +/− /ApoE −/− have accelerated atherosclerosis with increased caspase-1 pathway activation in inflammatory monocytes and atherosclerotic vasculature compared with ApoE −/− . Using a well-characterized cohort of people with HIV and tissue-banked aortic plaques, we documented that serum IL (interleukin)-18 was higher in people with HIV compared with non–HIV-infected controls, and in patients with plaques, IL-18 levels correlated with monocyte/macrophage activation markers and noncalcified inflammatory plaques. In autopsy-derived aortic plaques, caspase-1+ cells and CD (clusters of differentiation) 163+ macrophages correlated. Conclusions: These data demonstrate that expression of HIV is sufficient to accelerate atherogenesis. Further, it highlights the importance of caspase-1 and monocyte/macrophage activation in HIV atherogenesis and the potential of Tg26 +/− /ApoE −/− as a tool for mechanistic studies of HIV ASCVD. Abstract : Supplemental Digital Content is available in the text.